Biomarkers of palbociclib response in hormone receptor-positive advanced breast cancer from the PARSIFAL trial - Joan Albanell; Angelo Gámez Pozo; Carlos L. Arteaga; Meritxell Bellet; Federico Rojo; Abel González; Beatriz Bellosillo; Violeta Serra; Petra Gener; José Antonio Guerrero; Eileen Shimizu; Mario Mancino; et al. (npj Breast Cancer)
Abstract Currently, there are no clinically actionable biomarkers to predict patient to cyclin-dependent kinases 4 and 6 inhibitors (CDK4/6i) plus endocrine therapy for hormone receptor (HR)[+]/ human epidermal growth factor receptor 2 (HER2)[-] advanced breast cancer (ABC). Herein, we report an exploratory biomarker substudy (transFAL) from a subset of patients included in PARSIFAL, a phase II randomized clinical trial that evaluated first-line palbociclib plus fulvestrant or letrozole for HR[+]/HER2[−] ABC. No definitive biomarkers were discovered, however, worse outcomes were found with CDK6 postivity (p = 0.008), ER negativity (p = 0.008), high Ki67 (p = 0.04), and TP53 mutation (p = 0.04). ctDNA density (p = 0.036) and number of mutations (p = 0.033) at baseline were significantly higher for resistant patients. Our study reveals future directions to explore in the goal to determine biomarkers of response to CDK4/6i.